Drug resistance and plasmid profile of bacterial isolates from automated teller machine keypads in Benin city - Akinnibosun, FI; Adetitun, JA (Bangladesh Journal of Scientific and Industrial Research, 2019)
The purpose of this study was to investigate the drug resistance and plasmid profile of bacterial isolates from automated teller machine (ATM) keypads in Benin City, Nigeria. Samples were collected from the keypads of ATMs situated in banking premises and open access areas using stratified random sampling method at 5 different locations. Isolated bacteria were characterized by extensive phenotypic and biochemical identification procedures. Antibiotic susceptibility pattern and plasmid profile of the isolates were carried out using standard methods. The bacteria isolated were: Klebsiella sp., Pseudomonas aeruginosa, Proteus vulgaris, Escherichia coli, Micrococcus luteus, Bacillus subtilis, Staphylococcus aureus, Corynebacteria sp., Staphylococcus epidermidis and Streptococcus pyogenes. Each isolate exhibited marked resistance to the antibiotics, with multiple antibiotic resistance (MAR) index > 0.2. Escherichia coli showed the highest resistance (MAR index, 1) while Micrococcus luteus exhibited the least resistance (MAR index, 0.5) to the antibiotics used. Plasmid profile of the isolates revealed the presence of plasmids in the isolates, with a reduction in antibiotic resistance after plasmid curing in some isolates. This indicated plasmid-mediated resistance among majority of the isolates. From the results obtained, it is pertinent therefore, to adopt proper measures aimed at preventing outbreak of diseases associated with these multi-drug resistant bacteria isolated from ATM keypads. Bangladesh J. Sci. Ind. Res.54(3), 231-240, 2019